Types of Implicature in Piers Morgan vs Bassem Youssef on Palestine Treatment - Baiq Nurul Asikin; Abdul Muhid; Wiya Suktiningsih; Titik Ceriyani Miswaty; Agus Syahid (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study examines the use of implicature in an interview between Piers Morgan and Bassem Youssef discussing the Israel-Hamas conflict. It is based on the theory of implicature by H.P. Grice, which explains how speakers convey meanings beyond what is explicitly stated. The analysis focuses on conventional and non-conventional implicatures in their dialogue, demonstrating how Grice’s theory can be applied to understanding indirect communication in political discourse. By analyzing the use of irony, sarcasm, and other conversational strategies, this study offers insight into how these language techniques influence audience interpretation of sensitive issues. The method used in this research is qualitative. The data is taken from a YouTube interview titled “Israel-Hamas War: Piers Morgan vs Bassem Youssef Regarding the Treatment of Palestine.” The findings emphasize the importance of pragmatics in understanding how public figures communicate complex topics and shape public opinion.